Production of cellulase from Aspergillus niger and Trichoderma reesei mixed culture in carboxymethylcellulose medium as sole carbon - Dia Septiani; HERMAN SURYADI; Abdul Mun'im; WIBOWO MANGUNWARDOYO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Septiani D, Suryadi H, Mun’im A, Mangunwardoyo W. 2019. Production of cellulase from Aspergillus niger and Trichoderma reesei mixed culture in carboxymethylcellulose medium as sole carbon. Biodiversitas 20: 3539-3544. Cellulase is one of hydrolytic enzymes that breakdown cellulose into glucose. Cellulases are promising to be applied in natural products which may improve the yield of bioactive in plant extract through cellulose depolymerization. Cellulases from mixed culture of Aspergillus niger and Trichoderma reesei can produce a high cellulase activity because of the synergism activity among endoglucanase, exoglucanase, and also ?-glucoside. Cellulase production and partial purification of monoculture and mixed culture (1:1) of these fungi on carboxymethylcellulose media were investigated in this study. Total cellulase activity was measured by filter paper assay followed by protein estimation with Bradford method. The crude extract of Aspergillus niger monoculture has the highest cellulase activity (0.131 U/mL, P<005) followed by mixed culture (0.109 U/mL) and Trichoderma reesei (0.106 U/mL). The cellulase activity of partially purified cellulase from mixed culture significantly increased (0.335, 0.348, 0.374 U/mL, P<0.05) compared to crude extract along with stepwise addition of ammonium sulfate. Cellulase activity of mixed culture at 80% ammonium sulfate increase up to 2.238-fold and showed highest value (P<0.05) compared to monocultures. In conclusion, combination of Aspergillus niger and Trichoderma reesei fungi in carboxymethyl cellulose media followed by 80% ammonium sulfate precipitation can be a promising cellulase production with high cellulase activity.